Infotainment over Bluetooth / Mustaqim Mohd. Sumairi - Mohd. Sumairi, Mustaqim (2002)
This project deals with the concept of wireless technology and it is implemented using Bluetooth Technology device. The objective of this project is to analyze the application of the Bluetooth especially infotainment (information and entertainment) base on the chat application that is available right now. The Bluetooth Application & Training Tool Kit is used in this project as to make connection between two PCs. Visual C++ is the software used in building the software interface. For this project, it will only base on point-to-point connection as the device couldn't support point-to-multipoint connection. The project then is proceed by analyzing the chat application.